Layout design and users’ perception of different types of high-rise office buildings in Malaysia - Ismail, Lokman Hakim; Sibley, Magda; Abdul Wahab, Izudinshah; A. Elgadi, Ahmed (Trans Tech Publication Ltd, 2016)
There is an increasing demand for high quality office buildings nowadays. Occupants and developers of office buildings need to work together to create a healthy and inspiring working environment. These criteria engaged in the early stages of design can have a large impact on the performance of the finished building. This paper presents users’ perception of the general layout and adequacy of space in their office space. These features were investigated through observation and analysed data extracted from questionnaires. The aim is to investigate whether high-rise office buildings designed with a bioclimatic approach provide better working spaces than that of conventional office buildings. The assessments were made on detailed planning and the architecture of several buildings’ design approaches with the objective of consolidating perceptions on the working space and environment. The analysis shows that bioclimatic buildings are better rated than conventional buildings in terms of general layout, adequacy of space as well as flexibility of space. These factors might be connected to the size of all bioclimatic buildings, which are comparatively smaller than that of the conventional ones as well as the floor depths of all bioclimatic buildings, which are shallower than that of conventional ones. Due to these conditions, occupants in bioclimatic building are closer to the façade and might experience a better environment and space adequacy.